2022
DOI: 10.3390/jcm11247264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Cystatin C- and Creatinine-Based Estimated Glomerular Filtration Rate in the Follow-Up of Patients Recovering from a Stage-3 AKI in ICU

Abstract: Background: Acute kidney injury (AKI) in critically ill patients is associated with a significant increase in mortality as well as long-term renal dysfunction and chronic kidney disease (CKD). Serum creatinine (SCr), the most widely used biomarker to evaluate kidney function, does not always accurately predict the glomerular filtration rate (GFR), since it is affected by some non-GFR determinants such as muscle mass and recent meat ingestion. Researchers and clinicians have gained interest in cystatin C (CysC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Particularly, studies reported that CysC-based prediction equations were more precise and could benefit the earlier detection of renal impairment in specific subpopulations. In patients with reduced muscle mass because of amputations or in those with degenerative muscle disease, also in both children and obese patients, CysC might assess renal function [72, 73].…”
Section: “The Good”: Assess and Monitor Muscle Mass Nutrition And Phy...mentioning
confidence: 99%
“…Particularly, studies reported that CysC-based prediction equations were more precise and could benefit the earlier detection of renal impairment in specific subpopulations. In patients with reduced muscle mass because of amputations or in those with degenerative muscle disease, also in both children and obese patients, CysC might assess renal function [72, 73].…”
Section: “The Good”: Assess and Monitor Muscle Mass Nutrition And Phy...mentioning
confidence: 99%
“…Cystatin C has been shown to predict all-cause mortality and cardiovascular morbidity in a range of clinical settings including the general population [ 16 ], the elderly [ 17 ], and individuals with acute and chronic cardiovascular disease [ 18–20 ]. After critical illness which is near universally accompanied by profound muscle wasting, cystatin C provides a more accurate measure of kidney function [ 21 ] and is more strongly associated with ongoing risk of death [ 22 , 23 ]. However, cystatin C has not been extensively explored as a pre-operative predictor of AKI and other adverse outcomes after major surgery, despite many major-surgical candidates having low muscle mass.…”
Section: Introductionmentioning
confidence: 99%